Analysis of the Switching Mechanism of Hafnium Oxide Layer with Nanoporous Structure by RF Sputtering - Lim, Jongho; Baek, Myung-Hyun; Kwon, Min-Woo (Journal of semiconductor technology and science, 2025)
As the demand for advanced memory technologies grows, the development of next-generation memory devices is required. One promising candidate is resistive random access memory (RRAM), which is advantageous for high-density integration in three-dimensional vertical crossbar array architectures due to its simple metal-insulator-metal structure [1]. In this study, we fabricated an RRAM device and analyzed the characteristics of the HfOx insulating layer when it possesses a nanoporous structure. The HfOx insulating layer was deposited to induce the nanoporous structure by RF sputtering. When the HfOx insulating layer has a nanoporous structure, the device exhibits a minimum current existing at a specific voltage and rectifying properties. These characteristics result from the migration of oxygen vacancies and the presence of oxygen ions in the pores. Depending on the applied voltage magnitude, the internal electric field created by the negatively charged oxygen ions in the pores shifts the voltage point of the minimum current. In addition, the Schottky-like barrier modulation induced by migration of oxygen vacancies leads to a non-linear I-V switching behavior. The resistive switching mechanism observed in the nanoporous insulating layer plays a crucial role in enhancing the device’s performance. These findings provide valuable insights into understanding the electrical characteristics of other RRAM devices with similar structures. KCI Citation Count: 0